1994
DOI: 10.1029/93ja02288
|View full text |Cite
|
Sign up to set email alerts
|

Sudden impulses at low‐latitude stations: Steady state response for northward interplanetary magnetic field

Abstract: An examination of the response of the low‐latitude H component of the Earth's magnetic field during the passage of interplanetary shocks when the interplanetary magnetic field is northward reveals that this response can be understood quantitatively in terms of the compression of a simple vacuum magnetospheric model. The compression at the surface of the Earth at 20° latitude at noon in the absence of equatorial electrojet effects is found to be 18.4 nT/(nPa)1/2. Stations below 15° latitude and above 40° appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
149
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(170 citation statements)
references
References 20 publications
20
149
1
Order By: Relevance
“…Recently, in a statistical study, Francia et al (1999) analyzed some events occurring during northward IMF conditions and showed that the geomagnetic field horizontal component H at a low-latitude station (L'Aquila) responds very well to the SW pressure variations on a time scale of few minutes. The amplitude of the geomagnetic response was found to be linearly related to the change in the square root of the SW dynamic pressure, and its average amplitude (∼13 nT/(nPa) 1/2 ) is comparable with the values found by Russell et al (1994) and Russell and Ginskey (1995) at low and subauroral latitudes in the analysis of the sudden impulse (SI) response to the passage of interplanetary shocks. Moreover, the amplitude of the response was found to depend on local time, with greater values around local noon and midnight and a pronounced minimum during the local morning.…”
Section: Introductionsupporting
confidence: 69%
“…Recently, in a statistical study, Francia et al (1999) analyzed some events occurring during northward IMF conditions and showed that the geomagnetic field horizontal component H at a low-latitude station (L'Aquila) responds very well to the SW pressure variations on a time scale of few minutes. The amplitude of the geomagnetic response was found to be linearly related to the change in the square root of the SW dynamic pressure, and its average amplitude (∼13 nT/(nPa) 1/2 ) is comparable with the values found by Russell et al (1994) and Russell and Ginskey (1995) at low and subauroral latitudes in the analysis of the sudden impulse (SI) response to the passage of interplanetary shocks. Moreover, the amplitude of the response was found to depend on local time, with greater values around local noon and midnight and a pronounced minimum during the local morning.…”
Section: Introductionsupporting
confidence: 69%
“…We observed that the geomagnetic field I I . which is more complex than that observed for Sis at low latitude (with a single maximum around local noon [Russell et al, 1994]). Rather, it is very similar, although with a smaller excursion between minimum and maximum values, to the diurnal pattern observed at subauroral latitudes for Sis, which was interpreted in terms of superimposed effects of magnetopause currents and ionospheric Hall currents [Russell and Ginskey, 1995].…”
Section: Summary and Discussionmentioning
confidence: 58%
“…For southward IMF the opposite situation occurs due to the enhancement of the tail current and Region 1 current systems and to the triggering of substorms in the magnetotail [Russell et al, 1994b]. When the IMF is northward and the solar wind dynamic pressure suddenly increases, the increase in the H component magnetic field measured by low-and middle-latitude stations is governed by the currents on the magnetopause [Russell et al, 1994b] [Russell and Ginskey, 1995, Figure 7] which is somewhat similar to the case under study here, except that our observations are at middle-and low-latitudes. Russell and Ginskey [1995] postulated a steady or slowly varying current system associated with twin cells of largescale convection and apparently restricted to the dayside.…”
Section: Introductionmentioning
confidence: 99%